Understanding Rates of Genital Injury: Role of Skin Color and Skin Biomechanics - Sommers, Marilyn S. (J Forensic Leg Med, 2019)
PURPOSE. A series of studies suggest that non-Hispanic White women have significantly more injuries than non-Hispanic Black women after sexual assault and consensual sexual intercourse. One explanation for this difference is that the degree of skin protection may vary as skin mechanics and skin pigmentation vary. The aim of the study was to determine the association among genital-anal injury, skin color, skin viscoelasticity and skin hydration in women following consensual sexual intercourse when controlling for age, smoking history, body mass index (BMI), sun exposure, and health status. PROCEDURES. We employed a prospective cohort study design to enroll women 21 years of age or older at two study sites. They underwent two data collection sessions, baseline and follow-up after consensual sexual intercourse. Baseline genital-anal injury identification occurred with a standard forensic examination (direct visualization, nuclear staining with toluidine blue contrast, and colposcopy examination) and measurements of other variables (skin color, skin viscoelasticity, skin hydration, age, smoking history, body mass index [BMI], sun exposure, and health status). Participants were then asked to have consensual sexual intercourse with a male partner of their choice and to return for a second forensic examination for injury detection. Genital-anal injury was regressed on skin color, skin viscoelasticity, skin hydration, age, smoking history, BMI, sun exposure, and health status. FINDINGS. We enrolled 341 participants, 88 non-Hispanic White (25.8%), 54 non-Hispanic Black (15.8%), 190 Hispanic/Latina (55.7), and 9 Other Identities (2.6%). At baseline the genital-anal injury prevalence was 57.77% and at follow-up after consensual sexual intercourse, injury prevalence was 72.73%. External genital injury prevalence was associated with increased L* (lightness) values (Adjusted Odds Ratio [AOR] = 1.98, 95% Confidence Interval [CI] = 1.03, 4.04) and decreased skin elasticity (AOR = 0.96, 95% CI = 0.93, 0.99) at baseline. Increased skin hydration was associated with a significantly higher frequency of external, internal, anal, and total genital-anal injuries (Adjusted Rate Ratio [ARR] > 1.27) at follow-up. Also at the follow-up examination, Hispanic/Latina participants had significantly lower external genital and total genital-anal injury prevalence and frequency as compared to non-Hispanic White participants (AOR < 0.40). CONCLUSIONS. Our findings provide qualified support for the importance of skin color during the forensic examination. Women with lighter skin tones may have skin that is more easily injured than women with darker tones. In contrast, external genital injuries may be more easily identified in women with light as compared to dark skin, a situation that is important in both the health care and criminal justice systems. Additionally, women with decreased viscoelasticity and increased hydration may be more easily injured. These findings support the need to develop forensic procedures that are effective in people across the range of skin colors and to interpret forensic findings considering the innate properties of the skin.